(untitled) (Journal of the College of Basic Education, 2023)
There is less than one year left, and we are entering a century of tremendous development in quantity and quality.of the technological and informational scientific revolution that took place in the last decades of this century.Significant changes in many areas of life, including the educational fields, and today’s teacherHe differs in his duties from the teacher of yesterday. The children who go to school have their experience.Sensory has increased and complicated due to the development of means of communication (communicationmedia) and its complexity due to the use of advanced technological means and devices at homethe street and the school, and this was reflected in a change in the goals of education and the teacher’s mission.Methods of preparing it. The teacher has become prepared and trained according to educational and scientific methods and patterns.Developed, including systems analysis method, training competencies, educational technologies....etc.( 3 )The trends that emerged in the seventies of this century focused on competencies.Based Teacher (CBTE) – CompetencyEducation) to increase his efficiency, he is able to perform his professional role with high efficiency, due to thePerformance Standards Teacher Preparation (PBTE) objectives.Teacher Based Education (Performance) is what explains the teacher’s preparation.to anticipate change rather than follow it, in addition to providing the teacher with a set of educational competencies andThe necessary education to face the possible changes in the future in the light of developments.technological and scientific development, so that its role becomes clear in the enrichment and development of its material and methods.